Pengaruh Pelatihan Penanganan Korban Gigitan dan Sengatan Hewan Terhadap Pengetahuan Siswa/I Kelas 11 - Viana; Milkhatun; Rizal, Alfi Ari Fakhrur (Journal of Nursing Invention, 2025)
Background: Animal bites and stings are a significant public health issue in Indonesia, a country with high biodiversity. Students are one of the most vulnerable groups to animal bites and stings, especially in school environments that are often adjacent to forests or plantations. Objective: This study aimed to evaluate the effect of animal bite and sting first aid training on the knowledge of 11th-grade students at Madrasah Aliyah Miftahul Ulum Anggana. Method: A pre-experimental design with a one-group pretest-posttest design was used. A total of 35 students participated in the study. Result: The results showed that the mean knowledge score of the respondents before training was 18.47, and after training increased to 19.71. This increase in knowledge was statistically significant (p < 0.05). Conclusion: Based on the results of this study, it can be concluded that animal bite and sting first aid training is effective in improving the knowledge of 11th-grade students at Madrasah Aliyah Miftahul Ulum Anggana